Where she went - Forman, Gayle (New York : Dutton, 2011)
Adam, now a rising rock star, and Mia, a successful cellist, reunite in New York and reconnect after the horrific events that tore them apart when Mia almost died in a car accident three years earlier.
Sequel to: If I stay.
9-12.
Keywords: Interpersonal relations in adolescence -- Juvenile fiction; Emotional problems of teenagers -- Juvenile fiction; Rock music -- Juvenile fiction; Violoncello -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Realistic fiction